2021
DOI: 10.1093/femsle/fnab092
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B4 sewage-isolate induces pancreatitis after oral infection of mice

Abstract: Numerous serotypes which belong to the genus Enterovirus (EV) show variability in their virulence and clinical manifestations. They are also known to undergo changes caused by mutations and recombination during their circulation in the environment and the population. Various EV serotypes are prevalent in groundwater, wastewater, and surface waters. Our previous studies showed that oral infection induces pancreatitis depending on specific conditions, such as gravidity, in an outbred murine model. Our aim in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Throat swab samples from 3 CVB4-positive patients (Ct values ranged from 25 to 29) were used for viral culture. However, permissive cells commonly used to culture CVB4 from stool or cerebrospinal fluid, such as LLC-MK2 or RD cells [ 37 ], were not successfully cultivated. Therefore, in this study, eight other kinds of cell lines were used to select cells susceptible to pneumonia-derived CVB4 inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…Throat swab samples from 3 CVB4-positive patients (Ct values ranged from 25 to 29) were used for viral culture. However, permissive cells commonly used to culture CVB4 from stool or cerebrospinal fluid, such as LLC-MK2 or RD cells [ 37 ], were not successfully cultivated. Therefore, in this study, eight other kinds of cell lines were used to select cells susceptible to pneumonia-derived CVB4 inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…To sum it up, these findings provided further support for the association between CVB1 infection and meningitis, myocarditis, hepatitis, pancreatitis, and T1DM. In addition, previous research also found that different CVB4 isolates could induce different diseases (Benkoova et al, 2021), and CVB has a high frequency of mutations that may result in changes in pathogenicity (Beck et al, 1995); the high mutation frequency of the CVB1 strain might lead to hepatitis (Wang et al, 1998). In addition, the KM7-X29 P10 strain was as pathogenic as its original strain, KM7, in mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%